ANALISIS PUISI “SEMAKIN ERAT, SEMAKIN HILANG” KARYA KHOIRUL TRIAN DENGAN MENGGUNAKAN PENDEKATAN MIMETIK - Rina Nurfalah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research is motivated by the researcher's curiosity about the meaning contained in a literary work, namely poetry. Literary work is the result of an act, the result of thinking that can get something in the form of a play, both in the form of poetry and it can also be in the form of prose. The purpose of this study is to determine the results of the meaning of the poetry after using the mimetic approach. The method used in this research is a qualitative descriptive method, which is to present the results of the research by describing them using words. The results of the analysis of the poem "Getting Closer, Getting Lost" show that in this poem it has a meaning about feeling sad because you have to lose and the lesson from the poem is sincerity in accepting a real situation that is not in accordance with expected expectations. Based on the results of the use of the mimetic approach to the poetry "Increasingly, Increasingly Lost", it can be concluded that the use of a qualitative descriptive method using a mimetic approach to Khoirul Trian's poetry is suitable for analyzing the meaning contained in a literary work, namely poetry